Clinical study of NM441 in respiratory infection - Senju, Shoji; Watanabe, Kentaro; Yoshida, Minoru (Japanese Journal of Chemotherapy, 1996)
A new quinolone antimicrobial agent, NM441, was administered to 6 patients with respiratory infection to evaluate its clinical efficacy and side effects. 200mg NM441 was administered orally twice a day for 5-14days. All patients had chronic respiratory diseases. They consisted of 2 with idiopathic pulmonary fibrosis, 1 with pulmonary emphysema and bronchial asthma, 1 with pulmonary emphysema, 1 with obsolete pulmonary tuberculosis, and 1 with bronchiectasis. Diagnoses of respiratory infections based on these respiratory diseases were acute bronchitis, bacterial pneumonia, secondary respiratory tract infection, infected bulla, bacterial pneumonia and secondary respiratory tract infection, respectively. Its clinical response was excellent in 1, good in 1, fair in 1 and poor in 3. Bacteriologically, causative organisms were isolated in 2 cases. Moraxella subgenus Branhamella catarrhalis in one case was eradicated, and Pseudomonas aeruginosa in the other case was replaced with methicillin-resistant Staphylococcus aureus. Neither side effects nor abnormal laboratory findings were observed after administration of NM441.